Australia's 'No Jab No Play' policies: history, design and rationales - Katie Attwell; Shevaun Drislane (Elsevier, 2022)
Abstract Objective: Since 2014, five Australian states have enacted 'No Jab, No Play' policies requiring children to be fully vaccinated to attend childcare and early education services. We review the five policies and their implications for implementers - including healthcare and childcare service providers - and analyse factors that shaped the design of state policies. Methods: We employed documentary analysis and analysed key informant interviews in NVivo 12. Results: Our findings reveal similarities and differences between state provisions regarding exemptions, grace periods, responsibilities of service providers and sanctions for non‐compliance. We elaborate on five factors of influence that have shaped No Jab, No Play policies: i) impetus for change; ii) policy normalisation, growing concurrence and stringency; iii) increased co‐optation of childcare providers into vaccination governance; iv) policy influence and lessons; and v) partisan politics and the development of party ideologies over time. Conclusion: A range of factors contribute to how and why Australia's NJNPlay policies have taken their current forms. Implications for public health: NJNPlay policies impact families and healthcare providers as part of the broader policy ecosystem concerned with maintaining high immunisation rates in Australia. Increased coercion of parents over time has been tempered by partisan positions on exemptions for disadvantage.